2011
DOI: 10.3353/omp.15.45
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different surface roughnesses on the differentiation of MC3T3-E1 mouse osteoblasts in vitro

Abstract: Abstract:Background: The purpose of this study was to investigate the differentiation and maturation of osteoblasts on surfaces with different roughnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
2
4
0
Order By: Relevance
“…It has been reported that suitable surface roughness applied to culture plastic or titanium plates facilitates the differentiation and calcification of osteoblasts . The present study showed that, on the fiber laser‐roughened zirconia plates, Runx2 mRNA expression was significantly greater on day 3, followed by an increase in ALP activity on day 7, and an increase in OCN mRNA expression on day 14.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that suitable surface roughness applied to culture plastic or titanium plates facilitates the differentiation and calcification of osteoblasts . The present study showed that, on the fiber laser‐roughened zirconia plates, Runx2 mRNA expression was significantly greater on day 3, followed by an increase in ALP activity on day 7, and an increase in OCN mRNA expression on day 14.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the size of the cell, MC3 T3‐E1, ranged from 20 to 50 μm; hence, the BG powders with sizes of 12–17 μm granulated with 0.5 and 1.0 wt% PVA can be easily phagocytosed. Furthermore, the phagocytosed particles might activate innate immunity and induce cytotoxicity against cells 30,40,41 . Therefore, it is important to optimize the BG specimen with proper particle sizes to avoid the toxicity that targets different applications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cytotoxicity was examined using an MTT assay following the ISO 10993‐5 protocol 29 . Initially, osteoblast cells (MC3 T3‐E1) were cultured in a minimum essential medium (MEM) and seeded in 24‐well plates at a density of 2 × 10 4 cells/well 30 . Meanwhile, sterilized BG specimens granulated with four concentrations of PVA solutions were immersed in MEMs for 24 h. Extractions with various concentrations of 20%, 40%, 60%, 80%, and 100% were then added into each well.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen type I, was examined in this study due to the fact that it is the most abundant component of the extracellular matrix in vertebrates and it is synthesized only by a limited number of cell types, including osteoblasts and odontoblasts, qRT‐PCR analysis showed that the expression of collagen type I increased significantly from day 0 to day 16 but showed no significant difference among the groups at the same day of evaluation. It is worth mentioning that qRT‐PCR analysis for osteopontin and osteocalcin – late osteodifferentiation markers that indicate maturation and calcification – expression had also been performed but there was no significant expression for both genes in all of the groups (data not shown). Immunocytofluorescence (ICF) examination showed that Runx2 and collagen type I expression was also confirmed on the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Altering substrate's topography in which the cells are seeded and cultured has been proven by many studies to influence the shape and attachment of cells and their differentiation in various lineages. This phenomenon has been demonstrated in several types of cells; mesenchymal stem cells, MC3T3‐E1 cells and bone marrow cells, among others . Dalby et al and McNamara et al demonstrated that the use of substrates alone can be sufficient to promote changes in cells that are similar to the introduction of osteo‐promoting media.…”
Section: Introductionmentioning
confidence: 95%